Investigation of Self-healing and Mechanical Properties of Asphalt Mixtures Prepared with SBS and Waste Metal - Atici, Iremgul Bektas; Yalcin, Erkut; Yilmaz, Mehmet (Springer Heidelberg, 2023)
The impact of induction heating on the self-healing of asphalt mixture test specimens prepared with scrap metal and styrene-butadiene-styrene (SBS) modified bitumen was investigated in this study. In addition, the effects of waste metals used instead of aggregates in asphalt mixtures on the asphalt mixtures' mechanical properties were determined. To this end, asphalt mixtures were prepared to use two different percentages (inst aggregates of 50% and 100% aggregates) of waste metal in two different mill scale (cold mill scale and hot mill scale) and SBS in two different percentages (2% and 3%) to create prismatic and Marshall asphalt test specimens. Induction heating systems were used to determine self-healing properties. The samples were heated in five different heating times as 120 s, 100 s, 80 s, 60 s, and 40 s. To measure the performance of the recovery processing, five recovery cycles were performed for every asphalt sample. According to the results, the hardness of the mixtures, the mixes' fatigue life and load repetitions both shorten as the waste metal usage ratio in the asphalt mixtures increases. As both the amount of sludge and the amount of SBS in the asphalt mixtures increase, the maximum temperatures of the asphalt mixtures also increase. When the SBS ratio in the asphalt mixtures increases, the recovery rates increase. In addition, as the waste metal content in the asphalt mixture increases, an increase in HL values is observed. Finally, the general binding and rheological properties of SBS modified binders were evaluated.
Keywords: Induction heating; Waste metal; Mechanical performance; SBS